2010
DOI: 10.1007/s11273-010-9191-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic and mechanical control for an invasive wetland plant, Juncus ingens, and implications for rehabilitating and managing Murray River floodplain wetlands, Australia

Abstract: Wetlands are prone to increased invasion by plant species following changes in hydrologic regime, leading to shifts in plant community composition and potentially ecosystem function and health. In this paper, the ecology and potential control of Juncus ingens, a native wetland plant in the MurrayDarling Basin of south-eastern Australia, is investigated. J. ingens has benefited from altered Murray River hydrologic conditions by expanding its range and invading seasonally-flooded grassland and riparian habitats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Commonly, decreases in plant productivity, species richness, and diversity (Molina et al, 2003;Tuxen et al, 2011;Wang, Li, et al, 2015), as well as differences in belowground biomass allocation (Pierfelice et al, 2017) and species composition (Amores et al, 2013) were observed, with all of vegetation distributions orienting along a salinity gradient (Table S1). Upstream occurred with lower wave energy and tidal inundation, but the high inflow of nutrient-rich freshwater provided optimal conditions for P. australis stand to grow (Magee & Kentula, 2005;Mayence et al, 2010). Because the SOM input rate in soils decreased along the salinity gradient, the contents and storage of SOC and TN in a single P. australis-dominated community were significantly higher than those in mixed P. australis and S. salsa, single S. salsa, and tidal flat (Figure 3a,b; Figure S2a,b).…”
Section: Factors Controlling the Distribution Of Sommentioning
confidence: 99%
“…Commonly, decreases in plant productivity, species richness, and diversity (Molina et al, 2003;Tuxen et al, 2011;Wang, Li, et al, 2015), as well as differences in belowground biomass allocation (Pierfelice et al, 2017) and species composition (Amores et al, 2013) were observed, with all of vegetation distributions orienting along a salinity gradient (Table S1). Upstream occurred with lower wave energy and tidal inundation, but the high inflow of nutrient-rich freshwater provided optimal conditions for P. australis stand to grow (Magee & Kentula, 2005;Mayence et al, 2010). Because the SOM input rate in soils decreased along the salinity gradient, the contents and storage of SOC and TN in a single P. australis-dominated community were significantly higher than those in mixed P. australis and S. salsa, single S. salsa, and tidal flat (Figure 3a,b; Figure S2a,b).…”
Section: Factors Controlling the Distribution Of Sommentioning
confidence: 99%
“…Wakef.)] were reportedly able to survive clipping stress more often than immature individuals due to the amount of belowground biomass available to promote regrowth (Mayence et al 2010; Middleton 1990). Clipping directly targets aboveground biomass, so individuals or species with more belowground biomass may be more tolerant to clipping stresses than those with less belowground biomass.…”
Section: Resultsmentioning
confidence: 99%